AN EFFICIENT STRUCTURAL REANALYSIS MODEL FOR GENERAL DESIGN CHANGES AND BASED ON THE FLEXlBILlTY METHOD - Taye, Shifferaw (Zede Journal of Ethiopian Engineers and Architects, 2023)
Approximate structural retmolysis methods haw 10f'IJ/ bUff pursued in quest for ejJiclfmcy so a.t' to enhance the" practICal applicallon in the a.utument and verification oj desIgns Jollowmg design modiji£otions. TheJe hav~ been a/sigmficant practical importance with particular emphasi.t on design optImIzation of/arge-scall! structural systems in which thousands of design modifications need to ~ carned out during the search operatiOl'l to Idenllfyoptlmai S}'6lems. However, the cor!HquenllQ/ problems %ccura'Y and relioblilty call for the development of lH!tter.quality mathematical models that enh(mct computational qualIfy while keeping the compulalH'»1ol effort at a fraction of what might lH required If complete and flXDCt analysis wOuld be carried out. This paper presenl.1 an efficient structural nanalysl.f mnthematical model thai IS based ot1 the flexibility mflthod and exhIbits high approXImation qualities in e\1tlluating struclural responSflS of a nflwly proposed design from those of an initial trial design. The mathematical model to be presflnted here is a jlfl."r:lbllity-mflthod based binomlal·series approXImation of structural nspOIISes for a generaJ and unconditional coonge in dflsign cOordinates. It makes use of one set of resulu from a single exact analysIs usually carried out for the initial trial design. Nowl concepts of scaling aod norm minimization have been introduced 10 gain accuracy, efficiency, and reliability. l1u propose'd model has been compared with eXl.fting ones and also with eXDct analysis ootpUt.f and it has Jhown excellent approximating qualiti~ even under Jignificantly large design modijlcatiOllS. A numerical example has been presented. to show potential capabilities of the proposed model.